“Immuno-Transient Receptor Potential Ion Channels”: The Role in Monocyte- and Macrophage-Mediated Inflammatory Responses - Santoni, Giorgio; Morelli, Maria Beatrice; Amantini, Consuelo; Santoni, Matteo; Nabissi, Massimo; Marinelli, Oliviero; Santoni, Angela (Frontiers in Immunology, 2018)
Monocytes and macrophages play important roles in health and disease. They have a central role in protecting the host, as they clear pathogens and modulate other immune cell functions through the production of regulatory molecules. Their functions include immune surveillance, bacterial killing, tissue remodelling and repair, clearance of cell debris and more. Macrophages can have beneficial as well as detrimental effects on the outcome of several diseases depending on the microenvironment and the activation state of cells. Over the past few years, there has been an increasing interest in the expression and functions of ion channels, in particular of Transient Receptor Potential (TRP) channel family in immune cells. The 30 members of mammalian TRP channels are subdivided into TRPC, TRPV, TRPM, TRPML, TRPP and TRPA superfamily, and several members of TRP subfamily have been found to be functionally expressed in monocytes and macrophages. TRP are cation-selective channels that are weakly voltage-sensitive and diversely gated by temperature, mechanical force, electrophiles, ligands, and internal cues, such as membrane composition and pH, contributing to immune and inflammatory responses. The TRP channels play major roles in controlling several monocyte and macrophage functions such as phagocytosis, production of chemokines and cytokines, cell survival, polarization and so forth. In addition, they can also be potential therapeutic targets in a variety of inflammatory diseases. Thus, the goal of this review is to describe the role of TRP channels in the control of monocyte-macrophage functions in inflammatory and immune-mediated diseases.